2002
DOI: 10.1046/j.1365-2842.2002.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of altered occlusal guidance on condylar displacement

Abstract: This study investigated mandibular displacement and masticatory muscle activity during clenching in lateral occlusal position in relation to the lateral occlusal pattern. Twenty healthy human subjects (mean = 26.5 years) volunteered for this study. Metallic occlusal overlays were fabricated for the lower working side canine to second molar and non-working side second molar in order to simulate a canine protected occlusion, group function occlusion and bilateral balanced occlusion (balancing contact). Three-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 33 publications
3
30
0
3
Order By: Relevance
“…On jaw-closing, the incisor region typically laterodeviates about 5 mm, then moves medially as the food bolus engaged (Ahlgren, 1976;Gibbs and Lundeen, 1982;Miller, 1991). The mandibular condyles' lateral translation is minimal (0.4-0.6 mm) during chewing and other tasks (Gibbs and Lundeen, 1982;Payne, 1997;Okano et al, 2002;Otake et al, 2002;Miyawaki et al, 2004;Huang et al, 2006). During bolus compression therefore, the jaw rotates around its ipsilateral condyle as the contralateral condyle returns to its articular fossa (Gibbs and Lundeen, 1982;Gallo et al, 2000Gallo et al, , 2006Palla et al, 2003;Gallo, 2005;Miyawaki et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…On jaw-closing, the incisor region typically laterodeviates about 5 mm, then moves medially as the food bolus engaged (Ahlgren, 1976;Gibbs and Lundeen, 1982;Miller, 1991). The mandibular condyles' lateral translation is minimal (0.4-0.6 mm) during chewing and other tasks (Gibbs and Lundeen, 1982;Payne, 1997;Okano et al, 2002;Otake et al, 2002;Miyawaki et al, 2004;Huang et al, 2006). During bolus compression therefore, the jaw rotates around its ipsilateral condyle as the contralateral condyle returns to its articular fossa (Gibbs and Lundeen, 1982;Gallo et al, 2000Gallo et al, , 2006Palla et al, 2003;Gallo, 2005;Miyawaki et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is also widely accepted that one of the main tasks of occlusion is to ensure function with minimum muscular activity [12][13][14][15] thereby protecting the masticatory organ from dysfunction and ultimately from damage. Both cusp inclines and condylar path inclination seem to have a profound influence on the forces acting within the joints and the dentition [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that occlusions with anterior canine guidance allow less muscular activity and forces within the stomatognathic system during parafunction than occlusions with group function patterns and balanced occlusions [10][11][12][13][14][15][16][17][18][19]. For long-term success and stability it has been suggested that an occlusal concept be established which keeps the muscular activity of the patient at the lowest level and thereby prevents the stomatognathic system from dysfunction or possibly self-destruction [20,21].…”
Section: Introductionmentioning
confidence: 99%